1811. Use of Procalcitonin and Antimicrobial Stewardship Intervention to Limit Antibiotic Utilization in Patients Admitted to a Community Hospital with SARS-CoV-2 Infection. (15th December 2022) - Politis, Paula A; Oravec, Michael J; Hoisington, Lisa; Tan, Michael J; Agarwal, Shanu; File, Thomas M
Abstract: Background: Patients admitted to the hospital with SARS-CoV-2 infection are often treated with antibacterial agents in addition to antivirals, although bacterial co-infection in this population is uncommon. Overuse of unnecessary antibiotics can lead to suboptimal outcomes, including increased bacterial resistance, adverse events, and costs. Our Antimicrobial Stewardship (AS) Program routinely provides recommendations for appropriate therapy based on molecular/microbiologic tests, clinical findings, and procalcitonin (PCT). PCT can assist in differentiating bacterial from viral respiratory infections, and can be useful in the decision to discontinue antibiotic therapy if viral monomicrobial infection is suspected. The purpose of our quality improvement project was to review the appropriateness of antibiotics utilized for patients admitted with SARS-CoV-2 and to promote optimal patient care and AS at our institution. Methods: We performed a retrospective review of SARS-CoV-2 patients from our institution's COVID-19 registry for patients hospitalized from March 2020-April 2021. We compared patients with PCT < 0.25 ng/mL to those with PCT > 0.25 ng/mL and assessed differences in patient characteristics and disease presentation, including: age, gender, WBC, serum creatinine, culture results, disease severity, patient location, duration of antibiotics, length of stay, 30 day readmission and mortality. Characteristics were compared using descriptive statistics and appropriate inferential statistics. Results: Shown in Table 1. If prescribed antibiotics, median duration of antibiotic therapy was significantly reduced in the PCT < 0.25 group vs. the PCT > 0.25 group (2 days vs. 4.1 days). Median WBC, SOFA score, serum creatinine, and length of stay were significantly lower in the PCT < 0.25 group compared to the PCT > 0.25 group. Severity adjusted models showed significantly decreased duration and overall likelihood of antibiotic use for PCT < 0.25 vs. PCT > 0.25. 30 day readmission and 30 day mortality were significantly lower in the PCT < 0.25 group vs. the PCT > 0.25 group. Conclusion: Antibiotic utilization was reduced in patients admitted with SARS-CoV-2 infection and PCT < 0.25, and if prescribed antibiotics, duration was significantly shorter vs. those in the PCT > 0.25 group. Disclosures: Michael J. Tan, MD, FACP, FIDSA, Pfizer: Honoraria|Thermo Fisher Scientific: Honoraria Thomas M. File, Jr., MD, MSc, MACP, FIDSA, Nabriva Therapeutics: Advisor/Consultant|Nabriva Therapeutics: Honoraria.